Development of sarcopenia-based nomograms predicting postoperative complications of benign liver diseases undergoing hepatectomy: A multicenter cohort study - Bo, Zhiyuan; Chen, Ziyan; Chen, Bo; Yang, Jinhuan; Zhao, Zhengxiao; Yang, Yi; Ma, Jun; He, Qikuan; Yu, Haitao; Zheng, Chongming; Chen, Kaiwen; Wang, Yi; et al. (Frontiers in Nutrition, 2023)
Background Sarcopenia has a remarkable negative impact on patients with liver diseases. We aimed to evaluate the impact of preoperative sarcopenia on the short-term outcomes after hepatectomy in patients with benign liver diseases. Methods A total of 558 patients with benign liver diseases undergoing hepatectomy were prospectively reviewed. Both the muscle mass and strength were measured to define sarcopenia. Postoperative outcomes including complications, major complications and comprehensive complication index (CCI) were compared among four subgroups classified by muscle mass and strength. Predictors of complications, major complications and high CCI were identified by univariate and multivariate logistic analysis. Nomograms based on predictors were constructed and calibration cures were performed to verify the performance. Results 120 patients were involved for analysis after exclusion. 33 patients were men (27.5%) and the median age was 54.0 years. The median grip strength was 26.5 kg and the median skeletal muscle index (SMI) was 44.4 cm2/m2. Forty-six patients (38.3%) had complications, 19 patients (15.8%) had major complications and 22 patients (22.5%) had a CCI ≥ 26.2. Age (P=0.005), SMI (P=0.005), grip strength (P=0.018), surgical approach (P=0.036), and operation time (P=0.049) were predictors of overall complications. Child-Pugh score (P=0.037), grip strength (P=0.004) and surgical approach (P=0.006) were predictors of major complications. SMI (P=0.047), grip strength (P<0.001) and surgical approach (P=0.014) were predictors of high CCI. Among the four subgroups, patients with reduced muscle mass and strength showed the worst short-term outcomes. The nomograms for complications and major complications were validated by calibration curves and showed satisfactory performance. Conclusions Sarcopenia has an adverse impact on the short-term outcomes after hepatectomy in patients with benign liver diseases and valuable sarcopenia-based nomograms were constructed to predict postoperative complications and major complications.